National Women's Political Caucus of Alameda County Newsletter (1976)
This October 1976 newsletter from the National Women's Political Caucus of Alameda County outlines upcoming meetings, fundraising efforts, and election activities. It reports endorsements for regional and local candidates, fundraising support for women candidates including Jane Tolmach, and efforts to aid ERA ratification and women's political advancement. The State and National Steering Committee reports detail preparations for the 1977 national convention in San Jose, allocation of candidate support funds, and increased emphasis on legislative races in non-ERA-ratified state. The newsletter also highlights collaboration with allied organizations, fundraising successes, and internal governance matters, while encouraging members to vote and remain politically active.